2012
DOI: 10.1590/s0101-31222012000400010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between eggplant seed morphology and germination

Abstract: -Structural differences such as abnormalities, damage and free spaces in seeds may affect germination. The aim of this study was to study the relationship between eggplant seed morphology and seed germination. Ten seed lots of the eggplant cultivar Embu were evaluated by X-ray image analysis and the germination test. Seed image analysis was performed by Image Pro Plus ® software and the whole seed area and free space between the embryo and endosperm were measured. The internal seed area filled by the embryo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
4
12
0
7
Order By: Relevance
“…A presença de áreas livres no interior da semente pode prejudicar o potencial germinativo, pois estas podem significar menor quantidade de substâncias de reservas armazenadas, as quais são essenciais para o fornecimento de energia para os processos iniciais de germinação, pois a síntese de proteínas e a atividade respiratória inicial envolvem componentes armazenados durante a maturação das sementes (NONOGAKI et al, 2010 Mas a maior área livre interna nem sempre prejudicou a germinação de sementes, como a de berinjela (SILVA et al, 2012).…”
Section: Resultsunclassified
“…A presença de áreas livres no interior da semente pode prejudicar o potencial germinativo, pois estas podem significar menor quantidade de substâncias de reservas armazenadas, as quais são essenciais para o fornecimento de energia para os processos iniciais de germinação, pois a síntese de proteínas e a atividade respiratória inicial envolvem componentes armazenados durante a maturação das sementes (NONOGAKI et al, 2010 Mas a maior área livre interna nem sempre prejudicou a germinação de sementes, como a de berinjela (SILVA et al, 2012).…”
Section: Resultsunclassified
“…Several authors describe the importance of high quality of this seed as determinant in the production of the plant in the field. The degree of maturation of the seeds influences its quality, and the immature seeds have low vigor and germinative Power [3,4,5]. In the present study, the analysis of seed and seedling images has been shown to be efficient for the evaluation of the physiological and physical components of seeds.…”
Section: Introductionmentioning
confidence: 69%
“…Additional research showed the efficiency of the X -ray image analysis for the evaluation of the internal area of canafistula seeds [20], sweet pepper [10], eggplant [5], melon, pumpkin, and watermelon [8] and pumpkin [13].…”
Section: Radiographic Images and Free Internal Area Of Seedsmentioning
confidence: 99%
See 2 more Smart Citations